Exploring the Role of Literacy Coaches: A Case Study of Three Schools in Ontario (Alberta Journal of Educational Research, 2014)
This paper explores the role of literacy coaches in Ontario schools.  This case study uses qualitative research methods to provide a picture of what literacy coaching looks like in practice in three schools.  The literacy coaches had three main roles: to act as school literacy organizers, literacy leaders, and to provide support to teachers and principals.  Unlike the role of literacy coaches presented in the literature, the coaches in this study did not generally participate in observation and demonstration lessons and spent the majority of their coaching time performing organizational tasks.  This study makes recommendations for future research and provides suggestions for school boards implementing literacy coaching.Cet article explore le rôle des formateurs en alphabétisation dans les écoles de l’Ontario. Cette étude de cas repose sur des méthodes de recherche qualitatives et offre un aperçu pratique de la formation en alphabétisation dans trois écoles. Les formateurs en alphabétisation jouent trois rôles principaux : agir comme organisateurs de l’alphabétisation dans l’école, être chefs de file en alphabétisation et appuyer les enseignants et les directeurs. Contrairement aux formateurs présentés dans la documentation, ceux dans cette étude n’avaient pas tendance à participer aux observations et aux leçons pratiques. La plupart de leur temps était passé à accomplir des tâches organisationnelles. Cette étude offre des recommandations quant aux études à l’avenir et des suggestions pour les conseils scolaires en matière de la mise en œuvre de la formation en alphabétisation.